ANALISIS PERBANDINGAN KINERJA REKSADANA SYARIAH TERHADAP REKSADANA KONVENSIONAL (REKSADANA MAWAR) TAHUN 1997 – 2001 - Sofyan S Harahap (Media Riset Bisnis & Manajemen, 2003)
As one type of investment porfollos, the paper discusses the comperative of financial perfor- mance of syariah mutual fund and conventional mutual fund.Acase study, descriptive method is used as research method, it isexpected to describe about the character of syariah mutual fund and conventional mutual fund. Research was conducted from January 1. 1998 to De- cember 31, 2001. Syariah Investment fund is compared to Danareksa mawar (conventional) under one investment management by PT. Danareksa Investment Management. Perfor- mance evaluation was based on: Direct comparative method, Sharpe method, Treynor and Jensen method. The paper shows that đuring 1998-2001 the financial performance of "Reksadana Syariah" was better than Reksadana Mawar Convensional. However, based on our preleminary survey in the beginning of 2003, when IHSG increased, PT. Danareksa Invenstment Management liquidated the Danareksa Syariah. In rebound market shows that the financial performance of the Conventional Reksadana Mawar is better than Reksadana syariah.